DAMPAK BERBAGI INFORMASI RANTAI PASOKAN PADA KINERJA BISNIS BATIK DI THAMRIN CITY - Mailani Puspita; Dadang Surjasa (ITB AAS Indonesia Surakarta, 2023)
This research purpose is to analyze the effect of supply chain information sharing, operational performance, supply chain integration processes, supply chain agility on business performance in batik fashion in Thamrin City, Jakarta.The research design used is hypothesis testing. The sample used in this study were 151 batik traders in Thamrin City. The analytical method used is the Structural Equation Model (SEM) using SmartPLS. The results of the study show that supply chain information sharing, operational performance, supply chain integration processes affect business performance. Supply chain agility has no effect on business performance.